2019
DOI: 10.1055/s-0039-1688709
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life among University Students with Premenstrual Syndrome

Abstract: Objective To evaluate the quality of life among university students with premenstrual syndrome (PMS). Methods The cross-sectional study was conducted at the Faculdade Pernambucana de Saúde, in Recife, Brazil, between August 2016 and July 2017. Sociodemographic, gynecological, and lifestyle variables, and PMS occurrence, were investigated among 642 students. The short form of the World Health Organization Quality of Life (WHOQOL Bref) questionnaire was used to evaluate four domains of the quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 16 publications
6
24
0
3
Order By: Relevance
“…The results of our study agree with those reported in earlier studies, which indicate that regardless of ethnicity, women in their late teens and early twenties frequently experience such premenstrual complications [4, 19, 21, 24, 26, 28]. As to the severity, epidemiological surveys found a certain percentage (7.7–26.6%) of college students suffering from PMDD—a particularly severe form of PMS defined as a distinct premenstrual affective disorder [29, 30]. In this study, 122 students (61%) experienced at least one severe or extremely severe symptom in the premenstrual phase.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our study agree with those reported in earlier studies, which indicate that regardless of ethnicity, women in their late teens and early twenties frequently experience such premenstrual complications [4, 19, 21, 24, 26, 28]. As to the severity, epidemiological surveys found a certain percentage (7.7–26.6%) of college students suffering from PMDD—a particularly severe form of PMS defined as a distinct premenstrual affective disorder [29, 30]. In this study, 122 students (61%) experienced at least one severe or extremely severe symptom in the premenstrual phase.…”
Section: Discussionsupporting
confidence: 91%
“…Since none of them mentioned that their premenstrual symptoms disturbed academic performance, normal social activities, or relationships, we assume that their severity did not reach the level of severe PMS or PMDD. Although we need further investigation with prospective recordings to precisely evaluate premenstrual conditions, the study in hand reconfirms that a majority of college students are commonly aware of mind and body disharmony with a wide range of severity, in the late luteal phase as previous studies have presented [4, 21, 2830].…”
Section: Discussionsupporting
confidence: 64%
“…PMS is characterized by intense physical, cognitive, behavioral, and somatic symptoms in the luteal phase of the menstrual cycle [1,4]. These symptoms affect normal activities, interpersonal relationships, social activities, work efficiency, and educational productivity [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This study is important because it investigated the effects of health belief model‐based education for coping with premenstrual syndrome and acupressure on physical and psychological subscales of PMSS and quality of life and provided a model for future studies. Given the negative effects of premenstrual symptoms on women's school success, emotional well‐being, social activities, family relationships, and quality of life, the importance of this study could be understood better 4,6‐10 . Therefore, the use of these interventions and their inclusion in nursing care interventions are recommended to help women to reduce PMS symptoms.…”
Section: Implications Of Nursing Praticementioning
confidence: 99%
“…Many women are unable to cope with symptoms, such as changes in emotions experienced during the premenstrual period, nervousness, impairment of concentration, depressed mood, or insomnia 5,6 . Therefore, premenstrual symptoms may adversely affect individuals' attendance to courses, school success, social activities, and family relations 7,9 . In addition, the studies have also shown that premenstrual symptoms affects the quality of life negatively 5,9‐11 .…”
Section: Introductionmentioning
confidence: 99%